Analisis Usability Game Timpy Doctor for Kids: Penerapan Metode Heuristik untuk Anak Usia 2 – 4 Tahun dalam Desain Antarmuka - Endah Riana Endarini; Endarini, Endah Riana; Chaniago, Muhammad Fauzi Alexander (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study aims to analyze the application and relationship between the heuristic principles of 2 – 4 year old children and the Golden Rules of User Interface Design in the interface design of Timpy Doctor Games for Kids, focusing on the evaluation of navigation, icon clarity, visual instructions, and button interaction. This study used a heuristic evaluation approach and usability testing with five children aged 2 – 4 years, using direct observation, video recording, and field notes. The assessment was conducted using an instrument consisting of 79 game actions, 7 indicators, and scores of 1-5, and was analyzed descriptively by calculating the average value. The scope of the study was limited to one sub-game, namely tartar cleaning. The results showed that both design principles were consistently applied, as seen from the average interaction success rate of 4.94 and usability level of 4.57. Children were able to recognize icons, understand animation-based instructions, and complete most of the game actions. However, some issues were found, particularly in tasks requiring more complex fine motor coordination, such as connecting borders (2/5), administering drops (4/5), and grouping colors (4/5), as well as inconsistencies in instructions between tasks. The novelty of this study lies in the combination of two evaluation frameworks—child heuristics and the Golden Rules of User Interface Design—to analyze the UI of early childhood educational games, and its application to the previously unstudied Timpy Doctor Games for Kids game. These findings offer practical implications for game developers and child UX researchers in designing clearer, more consistent, and developmentally appropriate instructions for children. Further research could include expanding the number of participants, testing new game versions, and integrating other UX theories for more in-depth analysis.